Dearomatization and functionalization of tantalum bonded dialkoxide pincer ligands. (15th March 2018) - Fandos, Rosa; Otero, Antonio; Rodríguez, Ana M.
Graphical abstract: The reactivity of tantalum bonded dearomatized pincer ligands with methyl methacrylate is explored. The reaction yields new tetradentate ligands that easily react with proton sources such as water or triflic acid to render new functionalized pincer derivatives. Abstract: New tantalum derivatives with dearomatized pincer ligands have been prepared: [TaCp*Cl{κ 3 -N, O, O-(OCH2 )(OCH)py}] (2 ) has been synthetized by deprotonation of [TaCp*Cl2 {κ 3 -N, O, O-(OCH2 )2 py}] with LiNTMS2 and [Cp*Ta{κ 3 -N, O, O-(OCH2 )2 pyH}]2 (μ-O) (3 ) has been obtained by reaction of [TaCp*(OTf)2 {κ 3 -N, O, O-(OCH2 )2 py}] with Li[HBEt3 ]. The reaction of complex 2 or the analogous methyl derivative [TaCp*Cl{κ 3 -N, O, O-(OCH2 )(OCH)py}] with methyl methacrylate (MMA) render the corresponding tantalum enolates [TaCp*X{κ 4 -O, N, O, C-(OCH2 )(OCHMMA)py}] (X = Cl (5 ), Me (6 )). The Ta–O bond of the enolate fragment reacts selectively with water or with trific acid to render the corresponding tantalum hydroxide (7 ) or triflate (8 ), respectively. The structure of 3 has been determined by X-ray diffraction.